The Impact of Company Growth, Size, Profitability, and Leverage on Tax Avoidance with Good Corporate Governance as a Moderating Variable - Rizky Fitriana Rosalin; Agnes Advensia Chrismastuti (Jurnal Informatika Ekonomi Bisnis, 2023)
The research objective is to investigate the impact of Company Growth, Company Size, Profitability, and Leverage on Tax Avoidance with Good Corporate Governance as a moderating variable in Manufacturing Companies listed on the Indonesia Stock Exchange during the period 2017-2021. This study utilizes a quantitative method. The population and sample are obtained from the Indonesia Stock Exchange during the period 2017-2021. The research sample comprises 49 manufacturing companies listed on the Indonesia Stock Exchange during the period 2017-2021. Multiple linear regression analysis using the SPSS application is employed for data analysis. The results indicate that sales growth, company size, profitability, and leverage have a positive impact on tax avoidance, whereas good corporate governance weakens the influence of Company Growth, Company Size, Profitability, and Leverage on Tax Avoidance.